Assessment of Local Chicken Production Base Area in Minahasa Regency: A Location Quotient Approach - Hasrianti Silondae; Mujtahidah Anggriani Ummul Muzayyanah; Endang Sulastri; Budi Guntoro (Universitas Muhammadiyah Yogyakarta, 2024)
Local chickens have considerable potential to be developed and are reared as a source of animal protein and income. The production of local chickens is distributed across Minahasa Regency under a traditional free-ranging system. This study aims to assess the base area of local chicken farming and to determine the distribution of the superior commodity through the growth and share of local chicken production. Assessing the base area of the region for local chicken production can serve as the basis for the evaluation and design of policies. This study utilized a location quotient (LQ) approach in the empirical works in the regency and district. This analytical tool was applied to analyze the dynamics of the economic base in the cases of districts in Minahasa Regency, Indonesia. The analysis results denoted that 17 of 25 districts in Minahasa Regency ranked among the top base areas for local chicken development, as indicated by the highest LQ coefficients. Concerning the district potential base area, three districts fell into the superior category, four districts belonged to the static category, and 15 districts were in the potential category. This evidence reflects the potential and prospects of local chicken farming and its development plans as a leading commodity in Minahasa Regency. Encouraging farmers to maintain and develop livestock enterprises could support the provision of animal protein for consumption. There has been hope for the future of the local chicken commodity thanks to its inclusive development in resource-rich base areas.